Dependence of the incidence of emphysema on smoking history, age, and sex. Issue 5 (September 1972) - Anderson, J. A.; Dunnill, M. S.; Ryder, R. C.
Abstract : The relationship between the incidence of emphysema and smoking history, age, sex, and percentage bronchial mucous gland volume is investigated using the series of necropsy cases reported by Ryder, Dunnill, and Anderson (1971). Using those cases originating from hospital, it is shown that the incidence of emphysema is dependent on smoking history, age, and sex. Percentage bronchial mucous gland volume is not related to emphysema when the three other variables have been allowed for. Thus sex has an effect on the incidence of emphysema over and above the difference between the sexes in the occurrence of smoking. It is also shown that it is reasonable to extrapolate these conclusions from hospital necropsy cases to the general population.